Analysis on Demand of Indonesian Shrimp By International Market - Lusi Fausia; Wahyudi .; A Fahrudin; Nina Sri Sutami (Buletin Ekonomi Perikanan, 1993)
Demand elasticities in two major markets for Indonesian shrimp, The USA and Japan, were analyzed as a basis for identifying factors influencing import of the commodity by two countries. Price of tuna. per capita fish consumtion and import volume from India were found to be significant factors intluencing import of Indonesian shrimp by Japanese market. In the case of the USA market, the estimate model failed to explain the factors influencing import. Hygienic factor is supposed to be major factor responsible for the failure of Indonesian Shrimp to enterinto The USA market.